Keefektifan Metode Fitoremidiasi Menggunakan Tanaman Eceng Gondok Untuk Menurunkan Kadar COD (Chemical Oxygen Demand)Limbah Rumah Sakit - Zakiah, Fuad, Dwi Astuti SKM. M.Kes, Rezania Asyfiradayati, SKM, MPH (2017)
Liquid waste containing COD substances can affect human health and the environment. COD levels based on preliminary test results will be undertaken at the Hospital of PKU Muhammadiyah Delanggu of 199.3 mg/l, the results exceeded the water quality standard of waste. One way to do is to use the method fitoremidiasi with water hyacinth plants. The purpose of this study was to determine the effectiveness of the water hyacinth plant to reduce COD levels in PKU Muhammadiyah Hospital in Delanggu. This type of research study design true experiment with pretest and posttest with control group. Location of research at the Hospital of PKU Muhammadiyah Delanggu. Phytoremediation uses plants 4,6, and 8 plants hyacinth done for 7 days in 15 liters of waste water. Average yield- average effectiveness of COD levels after treatment are 46,15 %; 57,30%; 64,07%. The statistical test used is the One Way Anova. The results of the study obtained plants water hyacinth effective to reduce the COD on the water waste debgab doses effective 8 plant ( p-value 0,001).